Exploratory study among public servants in Kuching on the effectiveness of ACA’s aerogram complain form as a communication tool to combating corruption. (Case study: Anti-Corruption Agency Kuching Branch) / Marcel Bulan Ngabong - Ngabong, Marcel Bulan (2005)
Corruption is interpreted as gratification. Therefore gratification here means money, donations, loan, fee, reward, valuable security, property, any office, dignity, employment, contract of employment or services, payment, any valuable consideration of any kind, any discount, commission, rebate, bonus, and any forbearance to demand any money, any other service or favor of any description, any offer, any undertakings or promise.